Can Endogenous Monetary Policy Explain the Deviations from UIP - Annika Alexius (Uppsala University, Department of Economics, 2002)
The co-movements of nominal exchange rates and short-term interest rates as the economy is hit by shocks is a potential source of ex post deviations from uncovered interest rate parity. This paper investigates whether an established model of endogenous monetary policy in an open economy is capable of explaning the exchange rate risk premium puzzle. Time series on interest differentials and exchange rate changes are generated from the Svensson (2000) model. Uncovered interest rate parity is tested on the simulated data and the b-coefficients are investigated. For most realistic choices of parameter values, the b-coefficients are positive but much smaller than the unity value expected from UIP. It is however also possible to obtain large, negative b-coefficients if the central bank is engaged in interest rate smoothing.
urn:nbn:se:uu:diva-4448
Keywords: E52; F31; F41; 330; Monetary policy; Uncovered interest parity; Exchange rate risk premium; Geldpolitik; Währungsrisiko; Zinsparität; Theorie